Penyuluhan Pencegahan Stunting Pengabdian Masyarakat Di Desa Karanganyar Kecamatan Ambulu Kabupaten Jember - Aqlys, Shinta Ajeng Salyndri Hifdzul; Riqqah, RA. Lailita Aswanda; Ginting, Sonia; Tambunan, Agrerogates (Universitas Negeri Surabaya, 2025)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake or feeding that is not in accordance with nutritional needs. Stunting can also be defined as a condition where the body is short or very short based on the index of body length according to age or height according to age. One of the causes of stunting in toddlers is the lack of parental understanding of the fulfillment of children's nutritional intake. Therefore, this counseling activity aims to increase parents' knowledge of their toddlers' health. The method used is the descriptive-qualitative method with data collection through observation and interviews. Counseling activities were carried out at Karanganyarr Village Hall, Ambulu District, Jember Regency. From this counseling activity, it was found that most mothers in Karanganyar Village did not know what stunting was. With this counseling, it was concluded that there was an increase in mothers' knowledge of stunting. This can be seen from the emergence of several questions during the question and answer session. Keywords– stunting, stunting counseling, malnutrition